Simulation study for economic analysis of biogas production from agricultural biomass - Mel, Maizirwan; Hisham Yong, Ariff Syamin; Avicenna, Avicenna; Ihsan, Sany Izan; Hendroko, Roy (Elsevier, 2015)
A process of anaerobic digestion of agricultural biomass was simulated by SuperPro Designer software v 8.5 to analyze the costof production. The simulated project used fruits and vegetable wastes as a feedstock. The concentration of methane produced is55 % (v/v) from a total of 936.8 m3 . h–1 biogas and after purification, the concentration of methane is upgraded up to 95 % (v/v).The system was designed to treat the agricultural waste, and was able to reduce more than 60 % of the initial COD (chemicaloxygen demand). From the study, economic analysis shows that the profit margin is achieved at 11 % and the rate of return ofinvestment is at 12 % which gives a payback period of 8.2 years.